Memory failures of Everyday (MFE): Factor Analysis with Spanish population. - Montejo, Pedro; Montenegro, Mercedes; Sueiro, Manuel J.; Huertas, Evelio (Anales de Psicología / Annals of Psychology, 2013)
One of the most frequently used instruments to study everyday memory failures is the Memory Failures of Everyday Questionnaire (MFE). The objectives of the present study were: a) to examine the factor structure of the MFE, and b) to explore the relationship of the resulting factors with performance in tests of objective memory (Word Lists and Family Pictures of the Wechsler Memory Scale-III) and mood state (Goldberg Depression and Anxiety Scale), as well as with two general questions about memory complaints. Data were collected from a sample of 647 young adults (19-64 years). Factor analysis revealed three factors which explained 29.3 % of the total variance: Activities Recall, Communication Monitoring, and Recognition. The first two factors showed a higher positive correlation between them and a higher association with mood state and general memory complaints. In contrast, the recognition factor shows positive correlation with age and negative with objective memory performance.